Does control‐ownership divergence impair market liquidity in an emerging market? Evidence from China. (27th February 2014) - Chu, Xiaojun; Liu, Qigui; Tian, Gary Gang; Cahan, Steven
Abstract This paper examines how institutional characteristics of emerging economies influence the effect of control‐ownership divergence on market liquidity. We find that the divergence is negatively associated with liquidity and that this negative relationship is more pronounced in firms with more severe agency problems and information asymmetry. We argue that in an emerging market, the negative effect of the divergence on liquidity is worsened by state ownership and poorer shareholder protection, both of which result in more severe agency conflicts; we also find, however, that this effect is alleviated by the NTS reform, which aligns the interest of different shareholders.